Driving Public Service Innovation: Factors Influencing the Implementation of Mobile JKN Application in Indonesia - Ramdanis, Aulia; Priyambodo, Victoria Kusumaningtyas (International Journal of Business and Applied Economics, 2025)
The digital revolution has encouraged BPJS Health to launch the Mobile JKN application to improve access and quality of health services for the Indonesian people. This application offers easy access, efficiency, and transparency of health services. However, the adoption of Mobile JKN is still constrained by the level of user acceptance. The research uses the Model of Technology Acceptance (TAM) framework to examine elements that affect application use, such as perceived usefulness, simplicity of use, and trust in the application. The data collection technique uses convenience sampling for Mobile JKN users. Testing was carried out using the structural equation model (SEM) method with the SmartPLS test tool which was carried out by measuring the outer model and inner model. The results from 324 respondents showed that trust, security, and intuitive design of the application significantly increased user satisfaction and adoption intentions, reinforcing the importance of digital innovation in the health sector.